Teori Kritis Jurgen Habermas: Asumsi-asumsi Dasar menuju Metodologi Kritik Sosial - Tjahyadi, Sindung (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2003)
Multiculturalism the global cultural exchange, and the need of humanized communation are the real challenges for social sciences and social philosophy. Jurgen Habermas attemps to answer approach fundamental probelms. He built a comprehensive theory to analyze the relationship of knowledgem, science, politics, society, and culture in modern society. He found that we need a new approach to devolp an emancipatory science, a science which regard the human as the subject of change